An insight into post-independence Malaysian women’s well-being - Noor, Noraini M. (IIUM Press, 2009)
Since Independence in 1957, the structure of the Malaysian family has changed in tandem with changes in the wider global scenario. In post-Independence Malaysia, many women are employed with the dual-earner family gradually replacing the traditional family of the “father as breadwinner and mother as homemaker” prototype. While post-Independence Malaysian women are undergoing tremendous changes in their work and family lives, not much scholarly research has been carried out to document these changes and to examine their effects on the lifestyle and well-being of women. The collection of articles that is assembled in this edited volume provides an important contribution to an area that is becoming increasingly important to the well-being of Malaysian women and society. While the majority of the articles are based on the results of a quantitative survey of 639 urban women, charting and examining their changes in demographic, economic, communicational, social-cultural, and ICT areas, the final three articles consider women’s involvement in the scientific and technical fields, legal issues pertaining to the plight of foreign Muslim wives and the depiction of women in post-Independence Malaysian literatures. As such the papers contained in this volume cover a wide spectrum of issues pertinent to women and their well-being.